Broadly Tunable Self-injection Locked InAs/InP Quantum-dash Laser Based Fiber/FSO/Hybrid Fiber-FSO Communication at 1610 nm - M. A. Shemis; E. Alkhazraji; A. M. Ragheb; M. T. A. Khan; M. Esmail; H. Fathallah; S. A. Alshebeili; M. Z. M. Khan (IEEE Photonics Journal, 2018)
We report a self-injection-locked InAs/InP quantum-dash tunable laser with ∼11 nm (∼1602–1613 nm) tuning window for next generation multiuser ultrahigh capacity fiber/free-space optics (FSO)/hybrid fiber-FSO-based optical networks. A tunability of >18 independently locked subcarriers with ∼28 dB side mode suppression ratio (SMSR) and stable (±0.1 dBm) mode power is exhibited, and an estimated small injection ratio of ∼–22 dBm is found to sustain locking and SMSR. Error free transmission of 100 and 128 Gb/s externally modulated dual-polarization quadrature phase shift keying (DP-QPSK) signals over 20 km single mode fiber (SMF) and 16 m indoor FSO links are demonstrated across 8 and 4 individual subcarriers, respectively, thus covering the entire tuning range. Moreover, up to 168 (192) Gb/s successful transmission over 10 km SMF (BTB) and 176 Gb/s over 16 m FSO link is achieved on a ∼1610 nm subcarrier. Finally, a 128 Gb/s DP-QPSK transmission over 11 km SMF–8 m FSO–11 km SMF hybrid system is accomplished, thus paving the potential deployment of this single-chip, cost-effective, and energy efficient tunable light source in terabits/s next-generation passive optical networks.